2011
DOI: 10.1038/ncb2286
|View full text |Cite
|
Sign up to set email alerts
|

Mir193b–365 is essential for brown fat differentiation

Abstract: Mammals have two principal types of fat. White adipose tissue (WAT) primarily serves to store extra energy as triglycerides, while brown adipose tissue (BAT) is specialized to burn lipids for heat generation and energy expenditure as a defense against cold and obesity 1, 2. Recent studies demonstrate that brown adipocytes arise in vivo from a Myf5-positive, myoblastic progenitor by the action of Prdm16 (PR domain containing 16). Here, we identified a brown fat-enriched miRNA cluster, miR-193b-365, as a key reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
264
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(285 citation statements)
references
References 42 publications
16
264
3
2
Order By: Relevance
“…These inflammatory markers have direct effects on cellular metabolism, leading to decreased AT expandability, development of fibrosis, and dysfunction [8][9][10][11] . Similar to other inflammatory processes, white AT (WAT) inflammation is intrinsically linked to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…These inflammatory markers have direct effects on cellular metabolism, leading to decreased AT expandability, development of fibrosis, and dysfunction [8][9][10][11] . Similar to other inflammatory processes, white AT (WAT) inflammation is intrinsically linked to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, disruption of miRNA biogenesis by deleting fat-specific Dgcr8, a molecular anchor necessary for the recognition of pri-miRNA, results in defective BAT formation and severe cold intolerance (9). Recently, miR-193b/365 cluster was identified to be enriched in BAT and demonstrated as a key regulator to promote brown adipogenesis by targeting Runx1t1, a transcription factor that drives myocyte formation (10). In addition to suppression of myogenic lineage commitment, miR-196a promotes brown adipogenesis by inhibiting white adipocyte commitment (11).…”
mentioning
confidence: 99%
“…Noncoding RNAs are known to play a regulatory role in many developmental contexts, including adipogenesis, and several microRNAs have been identified that positively or negatively regulate adipogenesis (11,12). Recently we and others have identified a class of long noncoding RNAs (lncRNAs) (13)(14)(15).…”
mentioning
confidence: 99%